Pengaruh Dosis Pupuk Nitrogen terhadap Produktifitas Hidroponik Fodder Jagung (Zea Mays) - Moh. Mimbar Fauzi; Anifiatiningrum Anifiatiningrum (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2024)
This research is intended to identify the effects of nitrogen fertilizer on fresh production., dry material production (DM ), organic mater production ( OM ) crude pretein (CP) fodder mayze (zea mays). This research was carried out in the field lab of animal science departemen, Faculty of health and science, University Nusamara PGRI Kediri. research design in this study use a complete random design 4 treatment with 5 replicated. Treatment use concentration nitrogen fertilizer (T0 = 0 ml / l) ,( T1 =0.8 ml / l ), (T2 =1.6 ml / l ), (T3 =2.4 ml / l ). Studies show that different levels of nitrogen fertilizer can affacted to DM production (p < 0.01 ), OM production (p < 0.01 ) and CP production (p < 0.01) maize fodder (zea mays ).The conclusion of this study is that the use of different doses of nitrogen fertilizer has an effect on the production aspect of maize fodder (Zea mays )